Increased Frequency of Antigen-Specific Polyfunctional T Cells in Tuberculosis Patients. (22nd August 2013) - Syed Ahamed Kabeer, Basirudeen; Selvaraj, Anbalagan; Raja, Alamelu
Abstract : This study assessed the polyfunctional T cells in healthy household contacts (HHCs) and TB patients. This study also assessed the memory subsets responsible for the secretion of IFN- γ during the short-term culture with Mycobacterium tuberculosis antigens. Frequencies of CD4 + IFN- γ + TNF- α + T cells and CD8 + IFN- γ + TNF- α + T cells specific to M. tuberculosis antigens were significantly higher in TB patients compared to HHC. IFN- γ -secreting T cells, during overnight stimulation with M. tuberculosis antigens, belonged to effector memory subset with a CD45RA − CD27 − phenotype. However, the number of IFN- γ -secreting effector memory cells did not differ between HHC and TB patients.